PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN: (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023) - Rifa Amalia Ridho; Rismawandi Rismawandi (CV. Denasya Smart Publisher, 2024)
The purpose of this research is to determine financial performance, capital structure, company size, and sales growth on company value. The population in this research is food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2023 financial reports. By using a sampling technique, namely using a purposive sampling method with a total sample of 37 companies. This research uses multiple linear regression analysis methods with the help of the Statistical Package for Social Science (SPSS) Version 25 program. The results of the research show that financial performance and capital structure have a positive and significant influence on company value, company size has a negative and significant influence on company value, and Sales growth does not have a significant effect on company value.